Handbook for Markov chain Monte Carlo - Brooks, Steve, 1970- (Boca Raton : Taylor & Francis, 2011)
Provides a reference for the broad audience of developers and users of MCMC methodology interested in keeping up with cutting-edge theory and applications.
Includes bibliographical references and index.
uaj 22/10/2013
Loans
Keywords: Markov processes; Monte Carlo method